STABILITY AND CONSISTENCY ANALYSIS OF THE CG-5 GRAVIMETER BASED ON 31 DAYS OF CONTINUOUS OBSERVATION - Dadi Abdurrahman; Acep Ruchimat; Wiyono Wiyono; Setianingsih Setianingsih; Nabeel Ragheed; Asep Nugroho (National Standardization Agency of Indonesia, 2026)
Calibration of relative gravimeters is a critical step to ensure the accuracy and traceability of microgravity data, especially for instruments that have been out of operation for a long time, as they may suffer from mechanical stiffness and shifts in calibration parameters. The Scintrex CG-5 gravimeter used in this study had not been operated for several years, making it potentially unstable and unsuitable for direct use in field surveys without a proper burn-in and comprehensive calibration process. This research aims to determine the scale factor and its associated uncertainty through continuous measurements over a 31-day period at a single fixed location. The method utilizes Earth tide signals as a natural reference to evaluate the instrument’s response. Data from the 31st day of measurement show a very low instrumental drift of 0.010 mGal/hour, with an average reading noise of 0.048 mGal, and good stability in tilt and temperature. A linear regression between the drift-corrected gravity readings and the tidal model yields a scale factor of 1.0028 ± 0.0015 (k=1), with a coefficient of determination R² = 0.989. This indicates that the instrument responds to gravity changes with excellent linearity, despite a small deviation of 0.28% from the ideal response. The combined uncertainty was evaluated in accordance with standard metrological guidelines. The results demonstrate that after an extended burn-in and calibration period, the Scintrex CG-5 gravimeter has reached optimal performance and is ready for use in high-precision microgravity surveys. The single-point calibration approach based on continuous measurement proves to be an effective metrological method for routine performance evaluation of gravimeters, particularly for instruments reactivated after prolonged inactivity.